2021
DOI: 10.3390/nu13093059
|View full text |Cite
|
Sign up to set email alerts
|

Pulses Twice a Week in Replacement of Meat Modestly Increases Diet Sustainability

Abstract: The French food-based dietary guidelines recommend eating pulses at least twice a week and to reduce meat consumption. This study assessed the impact on the sustainability characteristics (nutrition, cost, environment) of individual diets of meeting the pulse guideline. Dietary data of 2028 adults from the Esteban survey were completed with the nutritional content (considering bioavailability on iron, zinc and protein), price and environmental impacts of foods. When the pulse guideline (i.e., 57 g/day) was not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 53 publications
2
11
0
1
Order By: Relevance
“…Overall, the results of this study are in accordance with earlier scenario studies from Sweden (21) and France (20) which also focused on the replacement of meat with legumes. Röös et al (21) found a 50% reduction of meat and corresponding increase in pulses to be beneficial regarding fibre and folate intakes.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Overall, the results of this study are in accordance with earlier scenario studies from Sweden (21) and France (20) which also focused on the replacement of meat with legumes. Röös et al (21) found a 50% reduction of meat and corresponding increase in pulses to be beneficial regarding fibre and folate intakes.…”
Section: Discussionsupporting
confidence: 90%
“…Röös et al (21) found a 50% reduction of meat and corresponding increase in pulses to be beneficial regarding fibre and folate intakes. Gazan et al (20) showed that the increase in the consumption of pulses (twice a week) in place of meat improved several nutritional indicators. However, our study provides an additional dimension by showing that the population shares below RI or AR diminished substantially for fibre and folate already in https://doi.org/10.1017/S1368980022002440 Published online by Cambridge University Press…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, pulses are a key component of sustainable diets. Like other legumes, pulses demonstrate biological nitrogen fixation which reduces dependency on commercial fertilizers [ 7 , 8 , 9 ]. About 2.9 million tons of common bean, pea, chickpea, and lentil are produced in the U.S. annually (5-year average of 2016–2020) [ 3 ].…”
Section: Introductionmentioning
confidence: 99%